THE RISING CHINA AND THE INDONESIAÃ¢â¬â¢S PESSIMISM TOWARDS ITS BILATERAL TRADE AGREEMENT WITH CHINA ON HIGH TECHNOLOGY SECTOR - Rahayu, Sri (Journal of S&T Policy and R&D Management, 2013)
This paper aims to investigate the Indonesias concerns towards its trade relationship with China especially on high-technology sector since UNCOMTRADE (2012) reveals that the trade deficit on high-technology products of Indonesia (towards Cina) has dramatically increased from 34 Million USD in 1992 to 5.3 Billion USD in 2011. By using three different kind of index calculations (Trade Complementary Index, Intra Industry Trade Index and Export Similarity Index), this paper has three main findings. First, Engaging export-import relationship with Cina hinders the development of Indonesias high-tech industry. The reason is that Indonesia only plays as a target market for Chinese hi-tech products. Second, the huge expansion of Chinese hi-tech products in the world market causes many difficulties for Indonesias hi-tech producers to create product differentiation. They are only able to imitate Chinese hi-tech products in order to survive in the world market. Last, the huge expansion of Chinese hi-tech industry leads this country to dominate the hi-tech regional production network in Asia. Without huge number of investment and innovation like today, it is impossible for Indonesias hi-tech producers to contribute more into the network.